Penerapan pembelajaran bermuatan sustainability di sekolah program adiwiyata untuk mendukung sustainable development - Haryanti, Eny Hartadiyati Wasikin; Kaswinarni, Fibria (University of Islam Malang, 2021)
The Adiwiyata program is implemented in order to realize responsible school citizens in efforts to protect and manage the environment through good school governance to support Sustainable Development. SMAN 3 Demak is one of the schools that organizes the Adiwiyata Program. Several activities that have been carried out to support Sustainable Development include environmental hygiene, waste management and reforestation. However, the learning process has not been carried out to support Sustainable Development, it is necessary to implement Learning Containing Sustainability. The purpose of this service is to provide teachers with: (1) insight and understanding of Sustainable Development (2) compilingÂ Learning Containing Sustainability. The methods used are counseling, workshop and mentoring. The results of the counseling activities on the understanding of Sustainable Development showed that 93.75% of the participants got a minimum score of 75 with complete criteria. As for the workshop activities onÂ Learning Containing SustainablityÂ (embedding the concept of Sustainable Development in learning materials) it was seen that 87.5% of participants were at least quite successful. The results of these activities have met the planned output targets. The mentoring activities for learning teachers have been carried out in accordance with the learning materials in their respective classes.